Diversitas Nyamuk di Sekitar Kandang Ternak di Kecamatan Mantikulore Kota Palu - Malonda maksud; Yusran udin; Hasrida Mustafa; Risti Risti (Loka Litbang Kesehatan Pangandaran, 2018)
Mosquito transmitted diseases are still a health problem in Indonesia, including in Palu City. Among the types of mosquitoes as a vector of the disease, there are to be zoophilic of animal blood. The study against the diversity of mosquitoes has been conducted in the area with the largest cattle population in Palu City, that Mantikulore District. The purpose of this study was to gain an overview diversity of mosquitoes around the cattle sheds. The study was carried out with free collection of mosquitoes around cattle sheds from 18:00 to 06:00 and one light trapping (CDC-Light Trap) at each location throughout the night from 18:00 to 06:00. Distribution diversity of mosquito around cattle sheds in five locations obtained 3 genus and 14 species of mosquitoes from a total of 1,464 captured mosquitoes. Culex vishnui is the most abundant mosquito in four research sites, namely in Kawatuna (44.44%), Poboya (82.18%), Tondo (66.95%), and Tanamodindi (38.58%). While in Talise the most abundant mosquito is Cx. quinquefasciatus amount 52.39%. The abundance of Cx. quinquefasciatus and Cx. vishnui was directly proportional to the frequency and dominance index. Shannon-Wiener diversity index shows the level of diversity in Kawatuna village, Talise village, and Tanamodindi village belongs to the medium, and in Poboya village and Tondo village belongs to low.